A Generational Perspective on the Software Workforce: Precocious Users of Social Networking in Software Development. Issue 1 (2nd January 2020) - Ghobadi, Shahla; Mathiassen, Lars
ABSTRACT: Software is the lifeblood of technological advancement, and it progresses not only through emerging technologies, but also through the contributions of new generations of developers who have distinct technology-related experiences. We describe our qualitative investigation into how developers, who began regularly using social networking technology at an early age (referred to as precocious users ), demonstrate distinct expectations about the goals of software development. We advance a theoretical perspective that explains how the increasingly socially infused nature of networking applications shapes generations of individuals — some of whom will go on to become creative developers in the software industry. Our perspective suggests software organizations can leverage developers who have been precocious users of more recent social networking technologies to reinforce intuitive usage, promote social impact, and re-energize experimentation and contribution to the software community. Our results also offer a comprehensive set of development goals that focus attention towards contemporary expectations about challenging usability and contribution to software ecosystems. We conclude by discussing how our methodological steps, data collection, and data analysis procedures empower future research to explore generational shifts in the career perceptions and competencies of the digital workforce.